2010
DOI: 10.1088/0067-0049/186/2/378
|View full text |Cite
|
Sign up to set email alerts
|

THE 22 MONTH SWIFT -BAT ALL-SKY HARD X-RAY SURVEY

Abstract: We present the catalog of sources detected in the first 22 months of data from the hard X-ray survey (14-195 keV) conducted with the Burst Alert Telescope (BAT) coded mask imager on the Swift satellite. The catalog contains 461 sources detected above the 4.8σ level with BAT. High angular resolution X-ray data for every source from Swift-XRT or archival data have allowed associations to be made with known counterparts in other wavelength bands for over 97% of the detections, including the discovery of ∼30 gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(203 citation statements)
references
References 53 publications
3
200
0
Order By: Relevance
“…In a similar energy range as IBIS, the Swift/BAT instrument provides a comparable distribution of the hard X-ray source population in the different classes Tueller et al 2010), with a slightly larger fraction of AGNs (∼60%) and a smaller fraction of X-ray binaries (∼25%) than in the 4th IBIS survey. These differences between the IBIS and BAT surveys can be attributed to different (and, to some extent, complementary) spacecraft observational strategies, INTEGRAL being mainly dedicated to Galactic plane scans and Swift covering more of the ecliptic pole regions and the sky outside the Galactic plane (see Bird et al 2010;Cusumano et al 2010;and Tueller et al 2010, for details).…”
Section: Statistical Considerationsmentioning
confidence: 93%
See 2 more Smart Citations
“…In a similar energy range as IBIS, the Swift/BAT instrument provides a comparable distribution of the hard X-ray source population in the different classes Tueller et al 2010), with a slightly larger fraction of AGNs (∼60%) and a smaller fraction of X-ray binaries (∼25%) than in the 4th IBIS survey. These differences between the IBIS and BAT surveys can be attributed to different (and, to some extent, complementary) spacecraft observational strategies, INTEGRAL being mainly dedicated to Galactic plane scans and Swift covering more of the ecliptic pole regions and the sky outside the Galactic plane (see Bird et al 2010;Cusumano et al 2010;and Tueller et al 2010, for details).…”
Section: Statistical Considerationsmentioning
confidence: 93%
“…In these tables, X-ray luminosities were computed from the fluxes reported in Voges et al (1999Voges et al ( , 2000, Saxton et al (2008), Krivonos et al (2009, Cusumano et al (2010), Krivonos et al (2010), Landi et al (2010), Rodriguez et al (2010), and Tueller et al (2010).…”
Section: Agnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawrence & Elvis (2010) reviewed the studies that dealt with the fraction of obscured AGN and concluded that the obscured fraction for the non-X-ray selected samples has a mean value of about 0.58 with a dispersion of ∼0.05. They also gave a rough estimate of 0.53 for the obscured fraction using the updated Swift/BAT hard X-ray catalogue (Tueller et al 2010), after applying the correction for missing Compton thick objects (Risaliti, Maiolino & Salvati 1999). The covering factors of a sample of 5281 WISE, UKIDSS and SDSS selected high luminosity quasars (L Bol > 10 46 erg s −1 ) with redshift <1.5 was determined by Roseboom et al (2013).…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…At present, the Burst Alert Telescope (BAT, Barthelmy et al 2005) aboard the Swift satellite (Gehrels et al 2004) is performing the most sensitive and complete survey of the sky in the hard X rays. The analysis of progressively longer periods provided with BAT survey data has produced in recent years catalogues and lists of Galactic and extragalactic sources (Markwardt et al 2005;Ajello et al 2008;Tueller et al 2008;Ajello et al 2009b;Tueller et al 2010). The largest (to date) hard X-ray catalogue, obtained from the reduction of 39 months of BAT survey data accumulated since its A&A 520, A47 (2010) launch, is the First Palermo BAT Catalogue (hereafter PBC39, Cusumano et al 2010).…”
Section: Introductionmentioning
confidence: 99%